MedLingua: A conceptual framework for a multilingual medical conversational agent - Galib Muhammad Shahriar Himel; Md. Shourov Hasan; Umme Sadia Salsabil; Md. Masudul Islam (MethodsX, 2024)
This study introduces a hybrid model for an advanced medical chatbot addressing crucial healthcare communication challenges. Leveraging a hybrid ML model, the chatbot aims to provide accurate and prompt responses to users' health-related queries. The proposed model will overcome limitations observed in previous medical chatbots by integrating a dual-stemming approach, P-Stemmer and NLTK-Stemmer, accommodating both semitic and non-semitic languages. The system prioritizes the analysis of cognates, identification of symptoms, doctor recommendations, and prescription generation. It integrates an automatic translation module to facilitate a smooth multilingual diagnostic experience. Following the Scrum methodology for agile development, the framework ensures adaptability to evolving research needs and stays current with recent medical discoveries. This groundbreaking idea aims to improve the effectiveness and availability of healthcare services by introducing an intelligent, multilingual chatbot. This technology enables patients to communicate with doctors from diverse linguistic backgrounds through an automated language translation model, eliminating language barriers and extending healthcare access to rural regions worldwide. • A simple but efficient hybrid conceptual model for advancement in smart medical assistance. • This conceptual model can be applied to implement a medical chatbot that can understand multiple languages. • This method can be utilized to address medical chatbot limitations and enhance accuracy in response generation.